Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/cctc.202001876
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin‐based NiFe Porous Organic Polymer Catalysts for the Oxygen Evolution Reaction

Abstract: Porphyrin‐based NiFe porous organic polymers (POPs) have been synthesized with good porosity and large BET surface areas (261 to 313 m2 g−1). These bimetallic POPs exhibit RuO2‐like OER activity, with the reaction for catalyst FeTAPP‐NiTCPP‐POP reaching a current density of 10 mA cm−2 at a low overpotential of 338 mV and with a small Tafel slope of 52 mV dec−1. FeTAPP‐NiTCPP‐POP was stable over a long period under reaction conditions. These bimetallic POPs exhibit better catalytic activity than their monometal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…1. The formation of the complex was confirmed by 1 H and 13 C NMR spectroscopy, provided in Fig. S1 and S2, † respectively.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…1. The formation of the complex was confirmed by 1 H and 13 C NMR spectroscopy, provided in Fig. S1 and S2, † respectively.…”
Section: Resultsmentioning
confidence: 81%
“…S5 in the ESI † except for a broad peak in the lower 2θ region, which clearly demonstrates an amorphous nature. 19 To establish molecular connectivity and the specific chemical environment of each carbon atom present in the POP framework, 13 C-CP MAS NMR spectroscopy was carried out on Ru@Bpy-POP (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yang and Hu et al reported a series of porphyrin-based NiFe POP catalysts (M 1 TAPP-M 2 TCPP-POP in Figure 11 ) for electrochemical OER [ 76 ]. In their study, four POPs including FeTAPP-NiTCPP-POP (M 1 = Fe, M 2 = Ni), NiTAPP-FeTCPP-POP (M 1 = Ni, M 2 = Fe), FeTAPP-FeTCPP-POP (M 1 = Fe, M 2 = Fe), and NiTAPP-NiTCPP-POP (M 1 = Ni, M 2 = Ni) were prepared via amidation reactions, and both the monomers and POPs were tested for electrocatalytic OER.…”
Section: Porphyrin-based Systems As Electrochemical Oer Catalysts For...mentioning
confidence: 99%
“…Porous organic polymers (POPs) [11][12][13] have quickly emerged as a suitable platform for heterogeneous catalytic transformations due to their excellent chemical stability, high surface areas, and tunable molecular skeletons. These attributes permit the integration of various CO 2 -philic units and organometallic linkers, such as metalloporphyrins, [14][15][16] to hydrogenate CO 2 to a chemical fuel or fine chemical in the presence of a suitable reductant. Hydrosilanes are great for reducing CO 2 due to the formation of thermodynamically stable SiÀ O bonds.…”
Section: Introductionmentioning
confidence: 99%